Conventional methods to prescribe exercise intensity are ineffective for exhaustive interval training - Bossi, A. H.; Cole, D.; Passfield, L.; Hopker, J. (European Journal of Applied Physiology, 2023)
Purpose To compare methods of relative intensity prescription for their ability to normalise performance (i.e., time to exhaustion), physiological, and perceptual responses to high-intensity interval training (HIIT) between individuals.